Resistance of Maize genotypes with different physical and chemical characteristics to the attack of Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) - SUÁREZ-GÓMEZ, HERNANDO; PEREIRA-SANTOS, JAMILTON; GÓMEZ DE LIMA, JOSÉ OSCAR (Revista Colombiana de Entomología, 1994)
Resistance to the maize weevil Sitophilus zeamais was determined for maize genotypes with modified protein quality (MPQ), carrying the Opaque-2 gene, for commercial materials and for some which are in the improvenment phase. The resistance evaluation was based mainly on the susceptibility index (SI) which considered the number of emerged weevils in the progeny F1 and the developmental period. The commercial maizes BR-105, BR-106, and BR-107 presented a low S.I. to the weevil's attack; this fact indicates that they have genetic sources which can be used in improvement programs, bearing in mind the resistance to the insect. Among the maize varieties bearing the Opaque-2 gene, the Yellow Flint HeO2 was more resistant than the IAC-1-02-IV. Maizes with MPQ presented a middle S.L. Neither of the physical or chemical characteristics considered was determinant for resistance in the genotypes to the attack of the weevil; it is possible that other genotype characteristics are responsible for the resistance.